2016
DOI: 10.1021/acs.jpca.6b00726
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Theory Study of the Microsolvated F(H2O) + CH3I SN2 Reaction

Abstract: The potential energy profile of microhydrated fluorine ion reaction with methyl iodine has been characterized by extensive electronic structure calculations. Both hydrogen-bonded F(-)(H2O)---HCH2I and ion-dipole F(-)(H2O)---CH3I complexes are formed for the reaction entrance and the PES in vicinity of these complexes is very flat, which may have important implications for the reaction dynamics. The water molecule remains on the fluorine side until the reactive system goes to the SN2 saddle point. It can easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…On a final note concerning the level of theory, a very recent set of calculations [42] observed that MP2 energy barriers for the S N 2 reaction of the attack of Fon the CH 3 I molecule were quite similar to those computed using the much more accurate CCSD(T). This result adds to our confidence in the calculations described above.…”
Section: Summary and Discussionmentioning
confidence: 80%
“…On a final note concerning the level of theory, a very recent set of calculations [42] observed that MP2 energy barriers for the S N 2 reaction of the attack of Fon the CH 3 I molecule were quite similar to those computed using the much more accurate CCSD(T). This result adds to our confidence in the calculations described above.…”
Section: Summary and Discussionmentioning
confidence: 80%
“…Also numerous theoretical studies investigated the effects of micro-solvation of the nucleophile. [175][176][177][178][179][180][181][182] Several studies showed that the presence of water molecules attached to the nucleophile reduces its reactivity in S N 2 reactions 174,177 as seen by experiments. Further insight was gained by investigating the effect of micro-solvation on individual intermediates.…”
Section: Effects Of Micro-solvation On the Dynamics Of Nucleophilic Smentioning
confidence: 99%
“…188 A trade-off between energetic and steric effects in the reaction of micro-solvated flouride ions F À with methyl iodide has been found in theoretical studies. Investigations of singly solvated F À (H 2 O) 174,181,192 have been extended up to three attached water molecules, F À (H 2 O) 0-3 . 173 It was found that the reaction coordinate does not cross the barrier of the fully solvated transition state complex.…”
Section: Effects Of Micro-solvation On the Dynamics Of Nucleophilic Smentioning
confidence: 99%
“…Zhang and co-workers found geometries along the F  + CH 3 I  CH 3 F + I  Walden-inversion pathway in microhydrated case at the MP2(ECP)/aug-cc-pVDZ(-PP) and DFT levels with various functionals and carried out single-point energy computations at the CCSD(T)(ECP)/augcc-pVTZ(-PP) level for the geometries optimized at MP2(ECP)/aug-cc-pVDZ(-PP) level. 83 I constructed a Walden-inversion energy diagram which is qualitatively the same, but the geometries are optimized at higher level. Similar optimizations at MP2 and DFT levels were carried out by Davico.…”
Section: Electronic Structure Theory Study Of the Microsolvated F‾(h2mentioning
confidence: 99%
“…84 Note that the barriers can be higher if the reactants are solvated by more molecules than the transition states, but the energies of the minima and transition states relative to each other are realistic on the energy diagrams shown in Figures 5.325.36. These diagrams are based on chemical intuition and prior work 83,86,87,89 and sometimes are supported by IRC † DF means density fitting computations. In the following section, I will discuss in detail these reaction pathways and the stationary points involved in them.…”
Section: Electronic Structure Theory Study Of the Microsolvated F‾(h2mentioning
confidence: 99%